Penggunaan Chlorhexidine Kumur dalam Perbaikan Indeks Kebersihan Gigi Pegawai Poltekkes Kemenkes RI Medan - Adriana Hamsar; Ety Sofia Ramadhan (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
The prevalence of dental caries in Indonesia is still high with a DMF-T value of 4.6 (Riskesdas, 2013). One of the causes of caries is plaque on tooth surface. Plaque that attached to the teeth provides nutrients for bacteria to grow, causes bacterial colonization, and provides an acidic atmosphere that will come in contact with the tooth surface, causing the enamel to dissolve and cause caries. Efforts to overcome this include through the use of mouthwash containing Chlorhexidine. Numerous studies have shown that Chlorhexidine has bactericidal and bacteriostatic effects. One of the pharmaceutical companies introduced Chlorhexidine products by adding Degluconate (DG) to increase its effectiveness. This study aims to examine the effects of Chlorhexidine-DG on dental hygiene. The research conducted was quasi experiment research. The population in this study were employees of Medan Health Polytechnic of Ministry of Health, with study sample of 100 people, divided into 2 groups, one group was given Chlorhexidine-DG, the other group was given mineral water as mouthwash. Data were analyzed univariately and bivariately using SPSS. The results of the bivariate analysis with Wilcoxon-Test, it was found significant difference in changes in the number of dental hygiene indexes (Plaque indexes) for the two groups. Chlorhexidine-DG and mineral water are equally effective against the dental hygiene index. But when compared between two Chlorhexidine-DG is more effective in affecting dental hygiene index than mineral water.